Effect of Copper Sulphate Exposure on the Oxidative Stress, Gill Transcriptome and External Microbiota of Yellow Catfish, Pelteobagrus fulvidraco - Shun Zhou; Qiuhong Yang; Yi Song; Bo Cheng; Xiaohui Ai (MDPI AG, 2023)
This study aimed to investigate the potential adverse effects of the practical application of copper sulfate on yellow catfish (Pelteobagrus fulvidraco) and to provide insights into the gill toxicity induced by copper sulphate. Yellow catfish were exposed to a conventional anthelmintic concentration of copper sulphate (0.7 mg/L) for seven days. Oxidative stress biomarkers, transcriptome, and external microbiota of gills were examined using enzymatic assays, RNA-sequencing, and 16S rDNA analysis, respectively. Copper sulphate exposure led to oxidative stress and immunosuppression in the gills, with increased levels of oxidative stress biomarkers and altered expression of immune-related differentially expressed genes (DEGs), such as IL-1β, IL4Rα, and CCL24. Key pathways involved in the response included cytokine-cytokine receptor interaction, NOD-like receptor signaling pathway, and Toll-like receptor signaling pathway. The 16S rDNA analysis revealed copper sulphate altered the diversity and composition of gill microbiota, as evidenced by a significant decrease in the abundance of Bacteroidotas and Bdellovibrionota and a significant increase in the abundance of Proteobacteria. Notably, a substantial 8.5-fold increase in the abundance of Plesiomonas was also observed at the genus level. Our findings demonstrated that copper sulphate induced oxidative stress, immunosuppression, and gill microflora dysbiosis in yellow catfish. These findings highlight the need for sustainable management practices and alternative therapeutic strategies in the aquaculture industry to mitigate the adverse effects of copper sulphate on fish and other aquatic organisms.